« Le lendemain je partais pour la Grèce » ‒ Dimitris Pikionis (1887-1968) : biographies et mémoires d’un architecte grec - Yannis Tsiomis (L'Atelier du CRH)
The biographies of influential modern and contemporary Greek architects appear more on occasional papers, bound to anniversaries or to conferences, than to university research or to fiction. The architect is not apparently a character deserving being a hero of a novel and it seems that he misses the heroic character, which since Vasari, marks historiography related to artists, painters, sculptors, architects. So we have a thin corpus on the subject which in the late decades begins to expand. Some architects’ biographies of the nineteenth centuries related to the “neo-classical style”, or regarding the post-independence architecture are some rare examples in the field. However, these exceptions are typological and morphological studies and do not investigate the biography of the architect. From the analysis of some papers regarding the life and the work of the architect Dimitris Pikionis, the designer of the walking path around the Acropolis in Athens, we try to enlighten the reasons justifying the absence of the architects’ biographical studies. Besides the Pikionis case study, it will serve as a possible biography, thanks to the use of various sources, putting in context historical and personal evidence, in order to understand what finally dominated over the making of the work of an architect-landscape designer